Survival and Environmental Stress Resistance of Cronobacter sakazakii Exposed to Vacuum or Air Packaging and Stored at Different Temperatures - Bai, Yichen; Yu, Haibo; Guo, Du; Fei, Shengyi; Shi, Chao (Frontiers in Microbiology, 2019)
The aim of this study was to evaluate the survival of Cronobacter sakazakii exposed to vacuum or air packaging, then stored at 4°C, 10°C, or 25°C, and the environmental stress resistance of vacuum-packaged or air-packaged bacterial cells were determined by subjecting the cells to reconstituted infant formula at 50°C, in acid (simulated gastric fluid, pH = 3.5), and in bile salt (bile salt solution, 5% (wt/vol). A cocktail culture of C. sakazakii desiccated on the bottom of sterile petri plates was air-packaged or vacuum-packaged and then stored at 4°C, 10°C, or 25°C for 10 days. The viable cell populations during storage were examined, and the vacuum-packaged and air-packaged cells (stored at 10°C for 4 days) were subsequently exposed to heat, acid, or bile salt. The results show that the populations of vacuum-packaged and air-packaged C. sakazakii were reduced by 1.6 and 0.9 log colony-forming units (CFU)/ml at 4°C and by 1.6 and 1.3 log CFU/ml at 25°C, respectively, in 10 days. At 10°C, significant reductions of 3.1 and 2.4 log CFU/ml were observed for vacuum-packaged and air-packaged cells, respectively. Vacuum packaging followed by storage at 10°C for 4 days caused significant decreases in the resistance of C. sakazakii to heat, acid, and bile salt conditions compared with air packaging. These results suggest that the application of vacuum packaging for powdered infant formula could be useful to minimize the risk of C. sakazakii.